(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Sansevieria cylindrica Bojer ex Hook. plant is an indigenous plant of the African continent subtropical province that is planted for decorative purposes in Egypt and India. It belongs to the Asparagaceae family. The plant is effective against treatment for caries, small pox, snake bite, stomach cancer, inflammatory conditions, influenza, cough, ear pain, swellings, diarrhoea, boils and fever and also this plant possess antihelmintic, antirheumatic, diuretic, laxative, vermifuge, antibacterial activity, antitrypanosomal activity, antioxidant and antidiabetic activities, antimutagenic effect, cytotoxic activity. Methods: The spectroscopic analysis i.e. UV, FTIR, and HPLC were used to analyse the bioactive components of Sansevieria cylindrica leaf extracts in ethanol and chloroform. Result: Peaks in the UV profile indicate that flavonoids, alkaloids, and phenolic compounds are present in the plant extract. FTIR analysis confirmed the presence of phenol, alkanes, secondary alcohol, aromatic amine, carboxylic acid, nitro compound, and halogen compound. Finally, flavonones, cinnamic acid derivatives, steroidal saponin, and phenolic compounds were noticed in the two plant extracts by HPLC analysis. Conclusion: The above three evaluations provide the basis for using Sansevieria cylindrica leaf as a herbal alternative for a variety of diseases.